Incidence and Comorbidity of Dementia with Lewy Bodies: A Population-Based Cohort Study - Sheng-Kung Yang; Weishan Chen; Chun-Hsien Su; Chung-Hsiang Liu (Behavioural Neurology)
Background and Aims. Dementia with Lewy bodies (DLB) is the third most common form of dementia. Epidemiological studies of DLB in Taiwan are scarce. In this study, we estimated the incidence of DLB and comorbidity in the population of Taiwan. Methods. Data were obtained from the Taiwan National Health Insurance Research Database (NHIRD). DLB patients between 2000 and 2013 were enrolled in assessments of incidence and comorbidity. Results. The incidence of DLB was shown to be 7.10 per 100,000 person-years (95% CI = 6.63–7.59), which increased with age. The average age at diagnosis was 76.3, and this was higher for males than for females. The comorbidity rates of hypertension and hyperlipidemia in DLB patients were higher in females than in males. Conclusions. Epidemiologic data from large-scale retrospective studies is crucial to the prevention of DLB.